Supplier Selection Proces: An Investigation and Implementation Action at Construction/Building Company - Hensmit, Andre (2008)
The investigation was carried out to identify and understand the key characteristic of supplier selection that is to be considered in the real experience by Construction Company in South East Asia, especially Indonesia. The goal of this project focuses on the selection supplier process and its approaches, how the company performing the co-partnership relationship with suppliers, and as well find out the reason fro accomplishing these factors. The project involves interviewing a company in Indonesia in order to produce the case study. The first chapter of this report will discuss about the background of the projects topic, and explain briefly the projects objectives and current condition of construction sector in Indonesia. The second chapter will discuss about the supplier selection, explaining supplier selection definitions and its factors, resource-based view theory, briefly explain about supplier selection approaches and its advantages and limitations. Next chapter will discuss about research methodology in order to achieve the aim and research objectives. This report will discuss the case study at Construction Company in Indonesia in chapter four. It includes supplier selection implementation, analyze the results and finding. Next chapter talk about author's argument on current supplier selection approaches, and also, the author gives recommendation to support one of the current supplier selection approaches. The last part of this dissertation conclusion, summarize all the findings on this project.